The Effect of Making People’s Puppets from Cassava Leaves on Prosocial Behavior in Students 5-6 Elementary Schools in Surakarta - Widayanti, Wahyu; Mufidah, Nur Laili; Tibyani, Yumna; Pratisti, Wiwien Dinar (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
This research was conducted to determine whether there is an influence of making puppets from cassava leaves on prosocial behavior in elementary school students. The method used in this research is Pre-Post One Group Design. The independent variable in this study is the making of puppets from cassava leaves, while the dependent variable of this research is prosocial. The subjects of this study were 207 people who were fifth and sixth-grade elementary school students in 8 elementary schools in Surakarta. The research flow used was the subject was given a pre-test using a scale for ± 10 minutes. The next step was treatment in the form of puppet making from cassava leaves in the experimental group for ± 30 minutes. During the treatment, the researcher made observations concerning the checklist observation sheet. The last plot is the post-test using the same scale as the pre-test but the item number is random. The results of this study statistically show the influence of making puppets from cassava leaves in increasing student prosocial. This is following the results of a descriptive analysis that shows the making of puppets from cassava leaves can improve the prosocial level of elementary school students who are in the low category by 14%, quite as much as 39%, and high by 47%.